Postopek vzpostavitve in testiranja lastne referenčne GNSS-postaje ( = Process of setting up and testing our own GNSS reference station) - Nikolaj Šarlah; Gašper Štebe; Oskar Sterle (Geodetski Vestnik, 2015)
In this paper, we describe the process of setting up a GNSS reference station. This is one option for capturing and managing spatial data in the local area. We demonstrate the method of mounting a reference station, as well as the required hardware and software for setting one up; the latter allows for real-time corrections that are transmitted in the RTCM. The coordinates of the reference station were determined using commercial (Topcon) and professional (Bernese) GNSS data-processing software. We demonstrate the differences between the results of both types of software. Taking example of the control points in the Celje area, we analyse the differences between the coordinates determined using our own GNSS reference station and the coordinates using the virtual reference station (from the SIGNAL network). We also discuss the differences between the coordinates measured using RTK (GNSS reference station and VRS/SIGNAL) and the control points. Based on our calculations of the deviations between the coordinates, we conclude that we can use our own reference station for baselines up to 15 km for the purposes of capturing utility data.